(Re)imagining race, gender, and class as choice in Octavia Butler`s "Wild Seed" - Jenkins, Tammie (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
For generations black writers have been searching for ways to insert their voices into Langer societal narratives of race, gender, and class. They began using the genre of science fiction to create characters and stories that embody, deconstruct, and rearticulate many of the taken for granted assumptions regarding aforementioned intersections. The field of black science fiction has enabled authors to (re) imagine socially constructed dichotomies of black/white, male/female, and rich/poor through their texts.
Keywords: "Wild Seed"; Butler, Octavia Estelle (1947-2006); (re)imagining; choice; race; gender; class